2017
DOI: 10.1177/1461444816688274
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and training in digital research: Researchers’ views in five social science and humanities disciplines

Abstract: This paper examines the views of researchers in five social science and humanities disciplines on their digital literacy and the training they need or have undertaken. Theoretically, the paper draws upon two competing conceptualisations of digital literacy: digital literacy as 'user skills' and digital literacy as 'user-technology interactivity'. Empirically, it suggests that social science and humanities researchers' understandings and evaluations of their digital literacy unfolds at two levels -the factual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
1
16
0
3
Order By: Relevance
“…Digital social research requires an interdisciplinary approach and will inevitably require some form of engagement with coding and data retrieval. And as Tsatsou (2018Tsatsou ( : 1253 notes, these areas of digital literacy are not necessarily ones that researchers with a non-digital humanities or social science background have been trained for to a sufficient degree. Tsatsou also identifies that the complexity of methodological issues in digital research and lack of highlevel technical skills for the humanities researcher could pose digital literacy challenges relating to ethics (2018: 1245).…”
Section: Towards Methodological Pragmatismmentioning
confidence: 99%
“…Digital social research requires an interdisciplinary approach and will inevitably require some form of engagement with coding and data retrieval. And as Tsatsou (2018Tsatsou ( : 1253 notes, these areas of digital literacy are not necessarily ones that researchers with a non-digital humanities or social science background have been trained for to a sufficient degree. Tsatsou also identifies that the complexity of methodological issues in digital research and lack of highlevel technical skills for the humanities researcher could pose digital literacy challenges relating to ethics (2018: 1245).…”
Section: Towards Methodological Pragmatismmentioning
confidence: 99%
“…On one hand, digital devices and the Internet enrich the children's experience, help them to preserve the old and make new connections, promote learning and personal development, and provide numerous opportunities for entertainment and performing various activities that the child would otherwise do but in more difficult ways (Amichai-Hamburger, McKenna, & Tal, 2008;Livingstone & Haddon, 2009). A series of studies within the digital literacy framework and the digital literacy theory (Glister, 1997;Tsatsou, 2018) have shown that the intensive Internet use -often operationalized as the amount of time spent on the Internet -is positively correlated with a number of desirable characteristics, which points to the enhancing and encouraging effect of digital technologies and the Internet use (Kuzmanović et al, 2019;O'Neill & Dihn, 2012;Popadić, Pavlović, Petrović, & Kuzmanović, 2016;Van Deursen & Helsper, 2018).The use of the Internet has also been recognized as one of the basic children's rights and, hence, preventing or restricting its use, with too little Internet, could be interpreted as violating children's fundamental rights and denying them the skills necessary for living in the 21st century (Livingstone, 2016). From this perspective, the motto that we can formulate as "the more (Internet time), the better" is quite appropriate.…”
Section: Highlightsmentioning
confidence: 99%
“…On the big data, it is permanently (re)constructed throughout the experience of the individuals (Baldi, 2017;Lupton, Pedersen, & Thomas, 2016), with profound implications in its control and access (Tsatsou, 2017). Dewey (2017, para.…”
Section: Social Researchmentioning
confidence: 99%